The best American infographics 2016 - Krulwich, Robert; Cook, Gareth 1969- (Boston Mariner Books, Houghton Mifflin Harcourt, 2016)
The latest addition to the celebrated Best American series, featuring the most creative and effective visualizations of data from the past year.
Includes bibliographical references.
Keywords: Visual communication -- United States; Communication -- Graphic methods; Information visualization -- United States; Charts, diagrams, etc -- Design; Computer graphics -- United States